Bestiary Motifs in Cycle of Stories by Pavel Krusanov “The King of the Head” - E. S. Tulusheva (Научный диалог, 2023)
The themes and poetics of the collection of short stories by P. V. Krusanov “The King of the Head” is characterized in the article. The collection is considered as a cycle with certain semantic and associative connections, secondary structural unity, genre, figurative-metaphorical and stylistic rapprochements, a through plot, cycle-forming motives. The novelty of the study is due to the tendency of modern prose to create this supertextual unity and, at the same time, insufficient knowledge of this phenomenon. The analysis of one of the leading cycle-forming motifs of the “King of the Head” - the bestiary motif, has been carried out. Each of the stories in the collection contains images of animals or metaphysical beings. Through them, the heroes of the works come into contact with another reality, paradisiac or infernal world, mortal space. The heroes of the collection cross the boundaries between their own body and consciousness and the bodies and consciousnesses of animals, or they are possessed by demonic forces. The images of animals are associated with the allegory of the spiritual path, along which, descending or ascending, the characters of the stories follow. A large number of zoomorphic comparisons and metaphors that capture the world, which is in a state of confusion, with the barriers between the living and the dead, bodily and mental, levels of consciousness are also used in the collection.